Picrorhiza kurroa Enhances β-Cell Mass Proliferation and Insulin Secretion in Streptozotocin Evoked β-Cell Damage in Rats - Kumar, Shiv; Patial, Vikram; Soni, Sourabh; Sharma, Supriya; Pratap, Kunal; Kumar, Dinesh; Padwad, Yogendra (Frontiers in Pharmacology, 2017)
Autoimmune destruction of insulin producing pancreatic β-cells leading to insulin insufficiency and hyperglycemia in type 1 diabetes mellitus. Regeneration of the insulin producing β-cells is one of the proposed treatment for type 1 diabetes and its insulin insufficiency. Picrorhiza kurroa is a medicinal herb and traditionally has been used for the treatment of various diseases. Previous studies reported the hypoglycemic potential of P. kurroa. However its potential role in β-cell regeneration and insulin secretion have not been fully investigated. Here we characterized the hydro alcoholic extract of P. kurroa rhizome (PKRE) and further studied its β-cell regeneration and insulin secretion potential in streptozotocin induced diabetic rats as well as in insulin producing Rin 5f cells. 1H-NMR revealed the presence of more than thirty metabolites including picroside I and II. Further, we found that PKRE treatment (100 and 200 mg/kg dose for 30 days) significantly (p ≤ 0.05) protected the pancreatic β-cells against streptozotocin (STZ) evoked damage and inhibited the glucagon receptor expression (Gcgr) in hepatic and renal tissues. It significantly (p ≤ 0.05) enhanced the insulin expression and aids in proliferation of insulin producing Rin5f cells with elevated insulin secretion. Furthermore it significantly (p ≤ 0.05) increased insulin mediated glucose uptake in 3T3L1 and L6 cells. On the contrary, in diabetic rats, PKRE significantly (p ≤ 0.05) decreased high blood glucose and restored the normal levels of serum biochemicals. Altogether, our results showed that PKRE displayed β-cell regeneration with enhanced insulin production and antihyperglycemic effects. PKRE also improves hepatic and renal functions against oxidative damage.